2008
DOI: 10.1007/s00467-007-0722-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of glomerular function tests in children with cancer

Abstract: Evaluation of renal function should be performed as part of the follow-up during and after chemotherapy in pediatric cancer patients. The aim of this study was to compare an isotope clearance method [isotope glomerular filtration rate (iGFR)] with alternative methods to determine GFR in such patients. Isotope GFR [(99m)Tc-labeled diethylene triaminopentoacetic acid (DTPA) or (51)Cr-labeled ethylenediaminetetra-acetate (EDTA)] was measured in 36 children (112 studies) and compared with simultaneously measured c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
3
19
4
Order By: Relevance
“…1,[5][6][7][8][9][10][11][12][13] Similar to these previous studies, the updated Sch correlated poorly with Tc-99m scan result in our cohort. 1,[5][6][7][8][9][10][11][12][13] Similar to these previous studies, the updated Sch correlated poorly with Tc-99m scan result in our cohort.…”
Section: Discussionsupporting
confidence: 89%
“…1,[5][6][7][8][9][10][11][12][13] Similar to these previous studies, the updated Sch correlated poorly with Tc-99m scan result in our cohort. 1,[5][6][7][8][9][10][11][12][13] Similar to these previous studies, the updated Sch correlated poorly with Tc-99m scan result in our cohort.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have reported that cystatin C can be used as an appropriate marker in monitoring the renal function, especially in children. 16,18,23 In fact, accurate and simple GFR measurement is crucial in elderly cancer patients. The results from the studies regarding adults are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Some studies have demonstrated that cystatin C was a better indicator in determining the renal function compared to creatinine in the patients receiving cisplatinbased chemotherapy. 8,[16][17][18] Furthermore, it was reported that cystatin C was found in higher concentrations in the tissues and body fluids of breast and prostate cancer patients and this was correlated with the aggressive form of the cancer. 19,20 The aim of our study was to evaluate the correlation of the serum cystatin C levels with the serum creatinine levels and GFR calculated by CockcroftGault and MDRD formulations in the patients who received cisplatin-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they showed that Cystatin-C values were important alternative to the measurement of GFR values. 29 In a study made in patients with varying degrees of renal failure and healthy volunteers, Trimarchi and his colleagues showed that, in patients whom GFR level is lower than 60 mL/minute, multiple blood sampling method showed the best correlation with Cystatin-C based Hoek formula. (r ¼ 0.82, P50.001).…”
Section: Discussionmentioning
confidence: 99%